PEMBOBOTAN PENILAIAN ASPEK KESELAMATAN DI ZONA KERJA PADA MASA PELAKSANAAN PROYEK PENINGKATAN JALAN - Dewa Ketut Sudarsana; Mayun Nandiasa; Ida Bagus Made Artamana (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2017)
Road safety is a topic that came out over the years and has now become a worldwideproblem. This can be picked up with the founding of the Decade of Action for Road Safety 2010-2020 by the United Nations. Efforts of prevention road safety during the implementation of roadimprovement has been specified in the path of contract execution. However, assessment of safetyaudits in the work zone on the road improvements has not been studied. Descriptive method used toidentify related attributes of safety in the work zone. Hierarchy and the weighting of each attribute isused the Analytical Hierarchy Process (AHP) method. The results obtained in, the weighting of the 4criteria division of work zones in sequence from the weight of greater are: the work zone; closerszone; initial taper zone and end taper zone by weight are: 59%; 27%; 9% and 6%. Weight rating ofalternative attributes for closers zone criteria is: road work warning signs: lane usage instructionssigns; closers zone distance; narrowing of lanes of the road warning signs and speed limit warningsigns, with their respective weights are: 46%; 23%; 15%; 11%; 5%. Weight rating attributesalternative to early taper zone criteria are: the installation of cone/guardrail; reflector at the initial ofthe work zone; minimum taper length requirement with respective weights: 53%; 30%; 17%.Assessment criteria attribute for the work zone are: minimum length of the work zone; the minimalwidth of the work zone; installation cone/guardrail; and the minimum distance between work zones,with respective weights: 70%; 15%; 9%; 6%. And the weight of attribute ratings for end zonecriteria is: the installation of cone/guardrail and followed with a minimum length end taperrequirements, with respective weights: 82%; 18%. Abstrak: Keselamatan Jalan merupakan isu yang mengemuka dari tahun ke tahun dan saat ini sudahmenjadi permasalahan global. Hal ini dapat dilihat dengan dicanangkannya Decade of Action forRoad Safety 2010-2020 oleh Perserikatan Bangsa Bangsa. Upaya pencegahan keselamatan dijalanselama masa pelaksanaan peningkatan jalan telah diatur dalam kontrak pelaksanaan jalan. Namuncara penilaian pemeriksaan keselamatan di jalan pada zona kerja pelaksanaan peningkatan jalanbelum diteliti. Metode deskriptif digunakan untuk mengidentifikasi atribut terkait aspek keselamatandi zona kerja pekerjaan jalan. Hirarki dan pembobotan penilaian masing masing atributmenggunakan metode Proses Hirarki Analitikal (PHA). Hasil rancangan pembobotan pada levelkreteria medapatkan 4 kreteria pembagian zona kerja secara teurut dari bobot kepentingan yanglebih besar adalah zona kerja; zona pendekat; zona taper awal dan zona taper akhir dengan bobotadalah 59%; 27%; 9% dan 6%. Bobot penilaian atribut alternative untuk kreteria zona pendekatadalah: rambu peringatan ada pekerjaan jalan; rambu petunjuk penggunaan lajur; jarak zonapendekat; rambu peringatan penyempitan lajur jalan dan rambu peringatan batas kecepatan, denganbobot masing-masing adalah: 46%; 23%; 15%; 11%; 5%. Bobot penilaian atribut alternative untukkreteria zona taper awal adalah: pemasangan kerucut/guardrail; pemasangan reflector padapertemuan taper awal dengan zona kerja; persyaratan panjang taper minimum dengan bobot masingmasing:53%; 30%; 17%. Penilaian atribut untuk kreteria zona kerja adalah: panjang zona kerjaminimum: lebar zona kerja minimum; pemasangan kerucut/guardrail; dan jarak antar zona kerjaminimum, dengan bobot masing-masing: 70%; 15%; 9%; 6%. Dan bobot penilaian atribut untukkreteria zona penjauh adalah: pemasangan kerucut/guardrail dan diikuti dengan persyaratanpanjang taper akhir minimum, dengan bobot masing-masing: 82%; 18%.Kata kunci: keselamtan, metode PHA, zona kerja, peningkatan jalan